Pengaruh Corporate Governance Perception Index Terhadap Kinerja perusahaan dalam Masa Krisis Ekonomi Global - Adi Suharna; Fifi Swandari (Universitas Lambung Mangkurat, 2013)
This research examines the influence of corporate governance toward corporate performance, in this case market performance and financial performance. The rating of corporate governance perception index (CGPI) for 2008 until 2010 by The Indonesian Institute for Corporate Governance is used to measure the corporate governance implementation and Tobin’s Q as a market performance measurement with Return on Equity (ROE) and Return on Assets (ROA) as financial performance measurement. The control variables used are leverage, age, type of industry and size of firm. This study is causal research which companies that scored CGPI and financial statement during 2008-2010 were drawn using purposive sampling method. Research data are pooling data which combines time series and cross sectional data during the observation period 2008-2010. This research employs a multiple regression to test hypothesis that corporate governance and corporate performance are positively related. From the first regression equation, the result of this study shows that there is influence between corporate governance perception index and market performance (Tobin’s Q) during crisis while the control variables have no effect on market performance unless leverage levels negatively affect the market performance of the company during the global economic crisis. The second regression equation shows that there is influence between corporate governance perception index and financial performance (ROE) during crisis while the control variables have no effect on financial performance (ROE). The third regression equation shows that there has no influence between corporate governance perception index (CGPI) and the control variables to financial performance (ROA) during the global economic crisis 2008-2010